NEGLECT OF AGRICULTURE, FOOD INSECURITY, HUNGER AND INSECURITY IN NIGERIA - Ugochukwu Amadi, Felix; Chinwe Ahamefula, Georgenia (African Journal of Social and Behavioural Sciences, 2024)
This paper titled, “Neglect of Agriculture, Food Insecurity, Hunger and Insecurity in Nigeria” began with an introduction. This was followed by the operationalization of concepts. Then the statement of the problem. Three research objectives were stated to guide the study namely: (1) To examine the reasons for food insecurity in Nigeria (2)To examine the nexus between food insecurity, hunger and insecurity in Nigeria (3) To proffer solutions to the issues of food insecurity and hunger in Nigeria. Conflict theory was adopted in developing the theoretical framework for this paper. The methodology adopted was a systematic content analysis of books, journals, and internet sources while the study used only secondary data as it was a qualitative study. Having answered the objectives of the study, the researchers made the following recommendations namely; that artificial intelligence and machine learning should be deployed across the country to measure crop conditions, water stress, soil moisture etc. in order to boost agricultural productivity and food security. That post-harvest losses can be significantly reduced by adopting green nanotechnology to preserve fruits and vegetables by using sachets containing polymers which diminish the natural degradation of fruits. That solar powered cold-rooms be provided in all 774 LGAs in the country to help farmers preserve their produce. That selective breeding, direct seeding, and bio fortification should be adopted in the country interalia.